The rise and fall of Turkey’s soft power discourse - Yohanan Benhaim; Kerem Öktem (European Journal of Turkish Studies)
Since the coming to power of the Justice and Development Party [Adalet ve Kalkınma Partisi, AKP] in 2002, Turkish foreign policy has witnessed significant changes. After the euphoric years of foreign policy pro-activism geared towards the global expansion of Turkey’s influence, domestic and regional developments have raised questions concerning Ankara’s capacity to achieve its ambitious foreign policy goals. Parallel to the “rise and fall” of Turkish foreign policy, a similar cycle can be observed regarding the discourse on Turkey’s “soft power”. This paper seeks to appraise Turkey’s “soft power” and “model” discourses by establishing the chronology of their emergence and highlighting the multidimensional structure of their production. The authors argue that the discourses on Turkey’s “soft power” are created within a triadic system of discourse production. This system works through the domains of think tanks, academia, and foreign policy actors in Turkey and beyond. These domains are bound to each other through reciprocal relations of interest and are negotiated by gatekeepers, i.e. well-connected persons of influence. Turkey’s “soft power” discourse is as much a product of Turkish foreign policy itself as it is a product of Turkey’s relations with the United States (US). Circulating through these different domains, and being appropriated by a large number of actors with differing and sometimes contradictory interests, these discourses, reconstructed by the authors in this study, are highly permeable, diverse, and unstable. For a brief period, they did, however, collectively contribute to the emergence of an almost hegemonic discourse on Turkey’s soft power, thereby reinforcing the AKP regime at the beginning of the 2010s.